A High Precision Method for Calcium Determination in Seawater Using Ion Chromatography - He, Hangqi; Li, Yifan; Wang, Shuyuan; Ma, Qianwei; Pan, Yiwen (Frontiers in Marine Science, 2020)
Calcium (Ca2+) is an important major cation in seawater, which is closely related to the oceanic biogeochemistry cycle. Direct and accurate determination of Ca2+ concentration is required for a more comprehensive study of the carbonate system in seawater. Due to the high background concentration of Ca2+ in seawater and small variances of Ca2+ during CaCO3 precipitation and dissolution process, a precision of better than 0.1% (of approximately ±10 µmol/kg) is very much desired for carbonate chemistry related studies. In this study, a simple, non-toxic and labor-saving technique using ion chromatography (IC) has been developed to determine Ca2+ in seawater with an overall precision of better than 0.1%. This proposed method, using IAPSO standard seawater as a reference, can get a result within 15 min and only requires a small sample volume (~1 ml). The concentrations and flow rates of the eluent have been optimized to achieve the best chromatographic separation (20 mmol/L and 1.0 mL/min were selected in this study). Our work suggests that sample dilutions have no discernible effect on Ca2+ determinations. However, the measured Ca2+ concentration shows a linear decrease with the increasing Mg/Ca ratio in samples, which could be corrected by a derived formula to achieve high accuracy within 0.1%. This optimized method has been applied to the analysis of Ca2+ distribution in Southwest Indian Ocean and the laboratory study on the calcite precipitation in seawater.